Analisis Tegangan dan Besar Defleksi pada Wall Jib Crane Kapasitas SWL 1 Ton Menggunakan Metode Elemen Hingga (Studi Kasus PT. Adiluhung Sarasanegara Indonesia) - Laila Radina Ningtyas; Mohamad Hakam; Widya Emilia Primaningtyas (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Analysis of the construction of a wall jib crane with a capacity of 1 ton was carried out by comparing the materials ASTM A36, ASTM A515, AISI 1008. The analysis was carried out using the finite element method with Fusion 360 software. From the results of the analysis, the material with the smallest deflection value is AISI 1008 of 9.98 mm with a von misses stress of 94,187 MPa, while in ASTM A36 and ASTM A515 the deflection value is 10.08 mm. The accumulated stresses and deflections that occur in each planned construction, both from manual calculations and simulations are declared safe, because the stress and deflection values that occur in the construction of the jib crane wall are below the allowable stress and deflection values. Based on the results of the design that has been carried out, the AISI 1008 material was chosen because it has a high safety ratio for wall jib crane construction.